Genetic Characterization of the Tetracycline-Resistance Gene tet(X) Carried by Two Epilithonimonas Strains Isolated from Farmed Diseased Rainbow Trout, Oncorhynchus mykiss in Chile - Christopher Concha; Claudio D. Miranda; Javier Santander; Marilyn C. Roberts (MDPI AG, 2021)
The main objective of this study was to characterize the tet(X) genes, which encode a monooxygenase that catalyzes the degradation of tetracycline antibiotics, carried by the resistant strains FP105 and FP233-J200, using whole-genome sequencing analysis. The isolates were recovered from fin lesion and kidney samples of diseased rainbow trout Oncorhynchus mykiss, during two Flavobacteriosis outbreaks occurring in freshwater farms located in Southern Chile. The strains were identified as Epilithonimonas spp. by using biochemical tests and by genome comparison analysis using the PATRIC bioinformatics platform and exhibited a minimum inhibitory concentration (MIC) of oxytetracycline of 128 µg/mL. The tet(X) genes were located on small contigs of the FP105 and FP233-J200 genomes. The sequences obtained for the tet(X) genes and their genetic environment were compared with the genomes available in the GenBank database of strains of the Chryseobacterium clade belonging to the Flavobacterium family, isolated from fish and carrying the tet(X) gene. The Tet(X) proteins synthesized by the Chilean Epilithonimonas strains showed a high amino acid similarity (range from 84% to 100%), with the available sequences found in strains belonging to the genus Chryseobacterium and Flavobacterium isolated from fish. An identical neighborhood of tet(X) genes from both Chilean strains was observed. The genetic environment of tet(X) observed in the two strains of Epilithonimonas studied was characterized by the upstream location of a sequence encoding a hypothetical protein and a downstream located alpha/beta hydrolase-encoding gene, similar to the observed in some of the tet(X) genes carried by Chryseobacterium and Flavobacterium strains isolated from fish, but the produced proteins exhibited a low amino acid identity (25-27%) when compared to these synthesized by the Chilean strains. This study reports for the first time the carriage of the tet(X) gene by the Epilithonimonas genus and their detection in fish pathogenic bacteria isolated from farmed salmonids in Chile, thus limiting the use of therapies based on oxytetracycline, the antimicrobial most widely used in Chilean freshwater salmonid farming. This results suggest that pathogenic strains of the Chryseobacterium clade occurring in Chilean salmonid farms may serve as important reservoirs of tet(X) genes.